Adapting Education: Navigating Hybrid Classrooms in The Post-Pandemic Era - Monika, Yunias; Kristanto, Septian Bayu (MO.RI Publishing, 2024)
Hybrid classrooms are designed to support collaborative learning experiences. This concept encourages students to actively engage within learning communities. This study investigates the applicability of hybrid classrooms in a university. Researchers utilized a CoI questionnaire adapted from Swan et al., (2008). It contains 36 items, all measured on a 4-point Likert scale. The questionnaires measure the three components of the CoI model. The participants consisted of accounting students who enrolled in Taxation courses in 2023, totaling 140 individuals. This result finds that students have effective social interaction, active engagement, and critical inquiry in the hybrid classroom. Students expressed a positive sentiment towards the hybrid classroom. The hybrid classroom undeniably has great potential for a flexible learning model for both students and educators in the future. While this study offers valuable insights into the perceptions of students regarding the hybrid classroom, the limitations, lack of demographic data, reliance on self-report measures, and absence of qualitative data, must be acknowledged when interpreting the findings.